CULTURE SHOCK AMONG FOREIGN STUDENTS: A CASE-STUDY OF THAI STUDENTS STUDYING AT UNIVERSITAS MUHAMMADIYAH PALEMBANG - Sulaiman, Masagus; Saputri, Kurnia (English Community Journal, 2019)
The phenomenon of culture shock has some impacts on  foreigners (i.e. psychological impact and intellectual impact), especially for foreign students studying in a new country. This research  is aimed at figuring out the dominant aspects of culture shocks faced by the three Thai students studying at Universitas Muhammadiyah Palembang and how they cope with it. Descriptive-qualitative method was used in this research.To collect the data, the researchers used interview and questionnaire. Coding technique was used in analyzing the data. The results showed two dominant aspects of culture shocks found, namely: academic shocks (i.e teacher’s role and attitude, poorly organized program and classroom organization, and local students’ attitude). and social shocks (i.e.women-men relationship, community bonding, habits in social gathering). Generally, the three Thai students coped with the shock by preparing mental and psychology, as well as learning academic destination.